Developing Open Education Literacies with Practicing K-12 Teachers - Kimmons, Royce M (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
This study seeks to understand how to use formal learning activities to effectively support the development of open education literacies among K-12 teachers. Considering pre- and post-surveys from K-12 teachers (n = 80) who participated in a three-day institute, this study considers whether participants entered institutes with false confidence or misconceptions related to open education, whether participant knowledge grew as a result of participation, whether takeaways matched expectations, whether time teaching (i.e., teacher veterancy) impacted participant data, and what specific evaluation items influenced participants’ overall evaluations of the institutes. Results indicated that 1) participants entered the institutes with misconceptions or false confidence in several areas (e.g., copyright, fair use), 2) the institute was effective for helping to improve participant knowledge in open education areas, 3) takeaways did not match expectations, 4) time teaching did not influence participant evaluations, expectations, or knowledge, and 5) three specific evaluation items significantly influenced overall evaluations of the institute: learning activities, instructor, and website / online resources. Researchers conclude that this type of approach is valuable for improving K-12 teacher open education literacies, that various misconceptions must be overcome to support large-scale development of open education literacies in K-12, and that open education advocates should recognize that all teachers, irrespective of time teaching, want to innovate, utilize open resources, and share in an open manner.